The Role of Multilevel Marketing (MLM) in Poverty Alleviation in Calabar – Cross River State, Nigeria: A Case Study of Forever Living Product (Nig.) Ltd - EFFIOM, LIONEL; Francis, Archibong Effiong (Advances in Social Sciences Research Journal, 2015)
This study assessed the role of multilevel marketing (MLM) in poverty alleviation in Calabar, Nigeria, using Forever Living Products (Nig.) Ltd. (FLP) as a case study. Structured questionnaires were served on a total of 300 respondent distributors of the company and the data generated were analysed using the Pearson Product Moment correlation statistical technique. The result of the hypotheses tested showed that there is a strong positive relationship between MLM and job creation on the one hand, and MLM and income generation on the other. Although MLM was found to be a means of wealth creation and a good source of residual income, it is by no means a business targeted at poverty alleviation. Significantly, 75% of respondents spent above the poverty benchmark (1.25/day) before joining FLP. Most MLM distributors were found to be confronted with the challenges of recruiting new downlines, and high cost of products. However cases of exploitation and inventory loading were minimal. The study recommends that government provide incentives to MLM companies to establish production plants in the country to exploit local economies and stem the tide of unemployment, among many other benefits. MLM companies should initiate business packages that are targeted at the poor. Keywords: Multilevel marketing, Forever Living Products, Poverty Alleviation, Job creation